Omnichannel Marketing Strategies For Tourism Destinations: Implications For Industry Practices - Olaf Tri Wilopo Simanjuntak; Eunike M. Gegung; Sonnya Marliani (Jurnal Inovasi Bisnis dan Kewirausahaan, 2025)
The advancement of technology has affected many sectors including the tourism industry. Adopting omnichannel marketing has become indispensable to enhance customer engagement and provide seamless, personalized experiences. Omnichannel marketing integrates multiple communication channels, such as websites, social media, mobile apps, and in-person interactions, into a unified system, offering a consistent and cohesive brand experience across all touchpoints. This strategy stands in contrast to traditional multichannel marketing, where channels often operate in isolation. Omnichannel marketing has been extensively studied in retail and e-commerce, while its application within the tourism sector is still emerging. This article explores the benefits and challenges of implementing omnichannel strategies in tourism destinations, drawing on case studies, industry reports, and academic literature. The findings indicate that omnichannel marketing can significantly enhance customer loyalty, increase revenue, and improve brand equity for tourism destinations. Examples such as Lake Toba in Indonesia, and Disneyland theme parks highlight the potential of omnichannel strategies to deliver integrated, frictionless experiences that increase customer satisfaction and drive repeat visitation. However, challenges such as data privacy concerns, adaptation of technology and budget constraints, must be addressed to elevate practices within the industry.